From Manual to Computerisation: A Case Study of Expenditure Cycle at Brainy Bookstore (Global Business Management Review (GBMR), 2022)
Brainy Book Store (BBS) had been operating successfully for over twenty nine years and had become a major text books provider in Alor Setar. The company had been selling books to nearby universities and college market. Its book lines included general books, academic books and library books. The company has only one retail outlet located in Malaysia Entrepreneur University campus, and employs twenty eight permanent staffs, five contract workers and ten student workers. For more than twenty years the company had enjoyed record profits. But during the last three financial years, the company has recorded net loss. Although market reaction to BBB had been positive from years to years, the overall profitability and efficiency of the company had fallen sharply since 2009, with the recording of an annual trading loss in the year 2012. As the General Manager, Danial feels that he should take immediate action in order to save the company from further losses. Based on his preliminary study, he discovers that there is something wrong with the company purchasing cycle. For the year ended 31 December 2012, it was found that approximately 95% of the books on consignment were not returned and the company had to bear huge ‘badstocks’ problems. Therefore, the management appointed a consultant to review its current purchasing and cash disbursement system as well as to propose a fully computerized purchasing system with the possibility of a web-based purchasing protocol linked to selected suppliers and cash disbursement system. From the investigation, the consultant reveals some flaws in the BBS expenditure cycle. Internal control weaknesses such as no segregation of duties, poor regulation enforcement and incomplete records need to be restored immediately so that the BBS could improve their financial performance in forging for a good profit again.